Education the Impact of Social Media on Mental Health and Sexual Violence Against Children in Primary School 14 Gurun Laweh, Padang - Yessy Markolinda; Wira Iqbal; Mery Ramadani; Fitri Yusya; Hanifah Aulia Rafdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Social media has created opportunities for children to become victims of bullying, sexual harassment, and other criminal activities. The target of this service activity is children who are in the transition phase to adolescence. This activity aims to educate school-aged children about the impact of social media on mental health and sexual violence against children at SDN 14 Gurun Laweh, Kota Padang. The education is delivered through lectures and discussions, complemented by pre-tests and post-tests to assess knowledge after receiving counseling on the impact of social media on mental health and sexual violence against children. These tests play a crucial role in evaluating the effectiveness of the program and guiding future interventions. Based on the difference in average scores before and after the counseling, students showed a significant improvement in three indicators: social media knowledge, which increased by 6,4; attitudes and actions, which changed by 4,2; and mental health and sexual violence awareness, which improved by 3,5. Preventive steps and interventions are essential to protect children from crime risk. Proper education for children by parents, teachers, and the surrounding community on how to use social media wisely and safely is critical to preventing sexual violence and reducing its negative impact on children's mental health.